PERANCANGAN MASJID JAMI DI DESA MELAYU KABUPATEN BANJAR - Muhammad Nazhif Rahman; Muhammad Tharziansyah (UNIVERSITAS LAMBUNG MANGKURAT, 2026)
Melayu Village is known for its strong Islamic teachings, which remain strong to this day. As time goes by, these Islamic teachings are beginning to fade. One way to maintain them is through community development. Generally, the mosque is the vehicle for community development at the village level. However, in reality, there is no mosque as a vehicle for community development. Therefore, the design of the Jami Mosque in Melayu Village was designed to be a vehicle for community development. For this purpose, the concept of Islamic Architecture was initiated, a concept that prioritizes the principles of Hablum Minallah, Hablum Minannas, and Hablum Minal'alam. Then, the method applied is Sense of Place or the essence of a place which is designed so that people both outside and inside the mosque feel comfortable and calm. The site is located in Melayu Village, Banjar Regency with an area of ​​​​30,000 m2, an area designed to accommodate community activities in economic, social, and educational. Based on the rules, the Jami Mosque is required to accommodate a minimum capacity of 1,000 people, so the mosque area applied is 1,664 m2 with one floor.